Informações de clientes sobre critérios de sustentabilidade utilizados na seleção de restaurantes - Fabrim, Carin Fernanda (My University, 2019)
An exploratory study was carried out to analyze customer information on sustainability criteria as a factor in the selection of restaurants. To achieve this, a questionnaire was created to collect the necessary data. The questionnaire was structured with closed questions (single and multiple choice) and open questions related to sustainable gastronomy as a criteria for restaurant selection by customers who were staying in two types of accommodation facilities located in two cities of the Serra Gaúcha (Rio Grande do Sul): Caxias do Sul (hotel) and the city of Garibaldi (hostel). The results let us conclude that there is a concern within the participants to consume organic foods (33.12%). This consumption is mainly because of health reasons (41.46%) and because they consider these foods tastier (20.56%). Only 17.42% of the indications were related to the consumption of these foods and concerns regarding the environment. It was also possible to identify that sustainable practices were not the most commonly used criteria for restaurant selection. Meal price was the main reason and had the highest number of indications (14.74%), followed by 13.25% pointing to ambience and comfort of the establishment. Only 4.30% of the indications were related to the adoption of sustainability as the main criteria of restaurant selection. The final conclusion therefore is that sustainability is not yet a major criteria factor in the selection of restaurants. The implementation of sustainable gastronomy practices by the food service industry however allows us to establish important relationships between the service offered and the client. Once adopting these practices, establishments can demonstrate a greater concern with the health of its consumers, with the impact caused by the sector to the environment, as well as stimulate the local or regional communities to adopt sustainable practices and thus promote the local culture and traditions, enhancing the economic performance of these communities.
No sentido de analisar as informações de clientes sobre critérios de sustentabilidade como fator de seleção de restaurantes, foi realizada uma pesquisa de caráter exploratório. Para tal, como técnica de coleta de dados, utilizou-se o questionário estruturado com perguntas fechadas (de única e de múltipla escolha) e abertas relacionadas à gastronomia sustentável como critério para seleção de restaurantes pelos clientes que estavam hospedados em dois meios de hospedagens localizados em dois municípios da Serra Gaúcha – Rio Grande do Sul: Caxias do Sul (hotel) e Garibaldi (hostel). Os resultados permitem concluir que existe uma preocupação por parte dos participantes da pesquisa em consumir alimentos orgânicos (33,12% das indicações). Esse consumo se dá por motivos de saúde (41,46% das indicações) e por considerarem esses alimentos mais saborosos (20,56% das indicações). Somente 17,42% das indicações dizem respeito ao consumo desses alimentos por haver a preocupação com o meio ambiente. Além disso, verifica-se que as práticas sustentáveis não são os critérios mais utilizados pelos clientes para a seleção de restaurantes, sendo o preço das refeições apontado com o maior número de indicações (14,74%), seguido por 13,25% das indicações para o conforto do restaurante. Apenas 4,30% das indicações estão relacionadas à adoção de ações sustentáveis como critério de seleção de restaurantes. Conclui-se que a sustentabilidade ainda não está internalizada como critério para a seleção de restaurantes. A implantação de práticas da gastronomia sustentável pelos serviços de alimentação permite estabelecer importantes relações entre o serviço oferecido e o cliente, uma vez que, ao efetivar tais práticas, o estabelecimento pode demonstrar maior preocupação com a saúde do consumidor e com os impactos causados pelo setor ao meio ambiente, bem como estimular as comunidades locais ou regionais na adoção de práticas sustentáveis e, dessa forma, promover a cultura e tradição, potencializando o desempenho econômico dessas comunidades.
Keywords: Turismo - Serra, Região (RS); Sustentabilidade; Restaurantes; Gastronomia; Tourism - Serra, Region (Brazil); Sustainability; Restaurants; Gastronomy